On the Inventory Cycle and the Instability of the Competitive Mechanism - Laroque, Guy (Econometrica, 1989)
This paper presents a model of the business cycle with perfect foresight where the mere presence of inventories is responsible for the appearance of the cycle. The basic assumption of the model is that the price system does not adjust instantaneously to its competitive value. Then inventory holding destabilizes the tâtonnement dynamics and creates the cycle. A Wicksellian cumulative process generates both the booms, where the real rate of return on cash is smaller than the natural rate of interest obtained by the inventory holders, and the recessions, where inventories are dominated by money balances.